DESULFURIZATION OF FUEL USING IONIC LIQUIDS - MAT SALLEH, MUHAMMAD ZULHAZIMAN (2014)
Ionic Liquids (ILs) have been recognized as a promising solvent for desulfurization of fuels. As the regulation of sulfur limit in each country becomes more stringent, the current technology for desulfurization is about to become more severe due to high operation cost and ineffective removal of aromatic sulfur compounds such as thiophene and its derivatives. This study is about exploring effective ways of removing sulfur from diesel using ILs which includes computational screening and experimental methods through extraction process.